Minimum quantity lubrication in micromachining: A greener approach - Zulkifli, Ahmad Syahmi Arham; Bahar, Rubina; Ariff, Tasnim Firdaus (IEOM Society, 2016)
Minimum Quantity Lubrication (MQL) uses minimum amount of lubricating fluid to reduce the friction between a cutting tool and the work piece. The conventional cutting fluid applied using flooding method causes high volume of the coolant wastage plus environmental damages due to disposal issues. MQL is suitable for machining operations including milling, turning, and drilling while surface modification processes are not very appropriate for MQL due to occurrence of particle sticking. For Micromachining, MQL has more opportunity as the heat generated in the small machining area can be smoothly transferred by MQL compared to flood cooling. Not much information are available about MQL performance and metal’s thermal conductivity. In this paper, study of Micro-milling using MQL is presented. Three different metals have been tested with same cutting parameters to observe the effect of MQL on metal’s thermal conductivity. Three different work metals are selected which are Copper, Aluminum alloy 1100 and Cast Iron with cutting parameters including depth of cut, feed rate, and spindle speed. Finally, surface roughness is measured to see the combined effect of thermal conductivity and MQL on the machined surface. It has been found that lower thermal conductivity metal is more suitable to employ MQL as the coolant method.